Identifying training load variables for elite youth soccer through a conceptual framework - Connolly, D.; Stolp, S.; Rampinini, E.; Coutts, A. J. (International Journal of Sports Physiology and Performance, 2026)
Purpose: The aim of this study was to guide the selection of load variables assessed within an elite-level academy player monitoring program through the application of a conceptual framework based upon previous literature and expert opinion.